2020
DOI: 10.1073/pnas.2007049118
|View full text |Cite|
|
Sign up to set email alerts
|

Massively parallel discovery of human-specific substitutions that alter enhancer activity

Abstract: Genetic changes that altered the function of gene regulatory elements have been implicated in the evolution of human traits such as the expansion of the cerebral cortex. However, identifying the particular changes that modified regulatory activity during human evolution remain challenging. Here we used massively parallel enhancer assays in neural stem cells to quantify the functional impact of >32,000 human-specific substitutions in >4,300 human accelerated regions (HARs) and human gain enhancers (HGEs),… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(109 citation statements)
references
References 48 publications
5
86
0
Order By: Relevance
“…In line with the fact that our data was not pre-filtered for putative regulatory regions, the proportion of active sequences we observed tends to be slightly lower than these previous studies. However, the magnitude of differential activity, as well as the fraction of differentially active sequences out of the active sequences was similar to previous studies 16, 2831, 8486 . At the same time, we were capable of measuring regulatory activity in regions that would otherwise be excluded by filtering for a specific set of marks.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In line with the fact that our data was not pre-filtered for putative regulatory regions, the proportion of active sequences we observed tends to be slightly lower than these previous studies. However, the magnitude of differential activity, as well as the fraction of differentially active sequences out of the active sequences was similar to previous studies 16, 2831, 8486 . At the same time, we were capable of measuring regulatory activity in regions that would otherwise be excluded by filtering for a specific set of marks.…”
Section: Discussionsupporting
confidence: 89%
“…With the exception of highly repetitive regions, which were removed from our library for technical reasons, the sequences we selected included all known modern human-derived fixed or nearly fixed variants (see Methods). Conversely, previous reporter assays and MPRAs on human intra- or inter-species variation used biased sets of variants by selecting sequences with putative regulatory function (e.g., eQTLs 28 , TF binding sites 16 , ChIP-seq peaks 29 , or TSSs 84 ) and/or regions showing particularly rapid evolution (e.g., human accelerated regions 30, 31, 85, 86 ). In line with the fact that our data was not pre-filtered for putative regulatory regions, the proportion of active sequences we observed tends to be slightly lower than these previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with other MPRA studies 4! (Tewhey et al 2016, Ulirsch et al 2016Uebbing et al 2021), most active sequences showed 5! relatively small effects, with only 17.1% of active sequences showing a LFC greater than 2 6!…”
Section: !mentioning
confidence: 97%
“…1C and Table S2). To study the evolutionary and functional impact of non-coding regulatory elements, we interrogated molecular signatures from genes associated with regions with human-specific substitutions (20,29,30) (fig. S3E and Table S3).…”
Section: Phenotypic and Molecular Adaptations Reveal Metabolic Human Acceleration Domainsmentioning
confidence: 99%